Travertinos y jasperoides de Manantial Espejo, un ambiente Hot Spring Jurásico: Macizo del Deseado, Provincia de Santa Cruz, Argentina Travertines and jasperoids of the Manantial Espejo, a Jurassic hot spring environment: Macizo del Deseado, Santa Cruz Province, Argentina - Horacio Echeveste (Latin American Journal of Sedimentology and Basin Analysis, 2005)
En este trabajo se analiza el origen y las relaciones entre travertinos y jasperoides intercalados en rocas volcaniclásticas jurásicas en el distrito argento-aurífero Manantial Espejo, ubicado en el borde sur-occidental del Macizo del Deseado, provincia de Santa Cruz, Argentina. Los cuerpos de travertino constituyen estratos delgados de hasta 60 cm de espesor de calcita micrítica finamente laminada, en ocasiones con estratificación rítmica de calcita y ópalo, asociados a depósitos de tobas de caída y tufitas de ambiente lacustre. En algunos afloramientos, los morfotipos reconocidos revelan que la precipitación del carbonato correspondía a sectores proximales relacionados a geisers y conductos de vapor, los cuales se orientaban a los largo de las fracturas que constituyeron los canales de circulación de fluidos. La posterior silicificación de los niveles carbonáticos produjeron jasperoides que se presentan como cuerpos tabulares subverticales y subhorizontales, estos últimos con características texturales similares a aquellas de sinters. La silicificación se originó tardíamente, posiblemente durante la etapa principal del régimen hidrotermal que generó las vetas portadoras de plata y oro. Los travertinos se formaron en un ambiente de hot spring, relacionado con fracturas de un sistema de cizalla conjugado orientadas entre N 20° a 45° E y N 20° a 40° O y constituyen las evidencias más tempranas de la presencia de un régimen epitermal asociado al proceso volcánico jurásico, en un régimen tectónico distensivo, en Manantial Espejo. In the last few years, an intense mining prospecting activity for gold and silver epithermal deposits has been carried out in the Deseado Massif, Argentina. As a result, many hot spring related deposits, of possible Jurassic age, have been detected. This paper describes the mineralogical and textural characteristics as well as the facies of a group of travertine and jasperoid outcrops occurring near the silver-gold carrying lodes in the Manantial Espejo prospect (Schalamuk et al., 1998). A genetic interpretation of the deposits is done on the basis of their structural, textural, and emplacement characteristics. Their possible relationship with the epithermal mineralization is also considered. The Manantial Espejo district is located on the southwestern area of the Deseado Massif, in the middle of the province of Santa Cruz (Fig.1). The area is almost entirely covered by andesitic and rhyolithic rocks of the Bajo Pobre and Chon Aike Formations, the product of a strong, bimodal volcanic activity of Jurassic age. This volcanic event developed in a back-arc tectonic environment linked to the opening of the Atlantic Ocean (Uliana et al., 1985; Riley et al., 2001). Acidic rocks prevail in the area, consisting on high-grade ignimbrites with ash fall tuffs, tuffites, and hydroclastic breccias (Fig. 2). Among them, the chemical and biogenic carbonate and silica deposits, are present (Fig.3). The travertine mantles can be up to 0.5 m thick and, in most of cases, they overlie tuffite layers. Typically, the rock is laminated in millimetrical to submillimetrical laminae of dense, hard, non porous micritic carbonate, displaying three types of lamination: parallel sub-horizontal; stromatolithic; and, «en echelon» (possibly, a terrace facies, Fig. 4). Sometimes, the laminated structure consists of a rhythmic deposit of calcium carbonate and opal (Figs. 5 a, b), unusual association in hot spring deposits, both recent and fossil (Jones et al., 2000a; Campbell et al., 2002; Canet et al., 2005). A variety of porous travertine, dominated by small, sub-spherical and columnar growths, of the microstromatolithic or the oncoid types. The travertine layers grade laterally to siliceous laminated jasperoids (sensu Spur, 1898 and Lovering, 1972), which make sub-horizontal mantles, 0.5 to 2.0 m thick, with identical sedimentary structures as those of travertines, although they are entirely formed of chalcedony, which is interpreted as the product of replacement of calcite into silica (Fig. 6a, b). Silicification occurred at a later stage, during the intense hydrothermal alteration accompanying the formation of the quartz veins carrying gold and silver. Some jasperoid outcrops show grossly stratified, rounded surfaces with domical structures, forming banks 0.2 to 0.4 m thick, and showing a more or less concentric layout which could correspond to the silicification of bio-built algal structures (Fig. 6b). The occurrence of small vents (Fig. 6e) show the water and steam outlets. Vertical, tabular, laminated bodies, filling fractures of NE-SW strike and slip up to 1,000 m, and 3 m thick (Fig. 6f, h). They are formed of chalcedony, displaying a vertical, banded and, at times, diffuse (Fig. 6g) or breccia like structure. The morphology of the travertines and associated jasperoids in the Manantial Espejo district are compared with travertines or hot spring deposits in general, of Quaternary or Recent (Guo and Riding, 1999; Chafetz and Guidry, 2003; Hancock et al., 1999). The analogies founded allowed to reconstruct, at least in part, the depositional environment of the studied rocks (Fig. 8). The sub-vertical, tabular bodies of banded silica, would correspond to subsurface levels of fissure ridges, where erosion has generally eliminated the surface deposits with sub-horizontal stratification overlying the faults. The northernmost end of the Ayelen Oeste «vein» (Fig. 6h) would correspond to the proximal zone of the discharge channel, very close to the fissure, since part of the sub-horizontal stratification next to the fracture (zone B in Fig. 8). This area represents the most active depositional environment, where the carbonate precipitation rate is higher. Figure 6e shows a fluid outlet vent in a spring zone (zone C, in Fig. 8). The «en echelon» stratification shows very similar characteristics to those of terraces and micro-terraces occurring in modern hot springs. Micro-terraces shown in Figure 5e, found near one of the fissure crests, could correspond to those formed laterally to the outlet channels (D, in Fig. 8). As to that shown in Figure 5f, associated to travertine with sub-horizontal, parallel lamination, could correspond to that formed in the edges of pools. With regard to the parallel lamination of micritic carbonate, occurring in most of the outcrops, it may correspond to the lacustrine rims (sensu Pentecost, 1995). This type of thin lamination, forming laterally extended banks, several tens of decimeters thick, would have formed on depressed surfaces, with a distal position relative to the spring zones. The rhythmic intercalation of thin opal laminae between the calcite layers occurring in some outcrops, reveals temporary changes in the physical-chemical conditions of the mineral precipitation, possibly seasonal temperature fluctuations. Finally, the observed stromatolites and microstromatolites (Fig. 5c, g, h) indicate the presence of microorganisms in the geothermal environment. Although there is no agreement among researchers about the organic or inorganic origin of these morphotypes in geothermal environments, it is admitted that algae and bacteria induce the precipitation of calcium carbonate. The stratigraphic position of the calcareous levels identified in Manantial Espejo show that the hot spring environment began to develop early in the district, associated to an extensional tectonic regime coincident with the La Frisia or Zanjón del Pescado System (Reimer et al., 1996) which caused fracturing (direct faults) N 20° to 45º E, and N 20º to 40° W, as a consequence of aó1 located around 0°. The produced faults, made the main hydrothermal fluid circulation channels (barren) which, after reaching the surface and losing the dissolved CO2, precipitated the calcium carbonate. The migration of the maximum stress (anti clockwise, at 315°) produced a new stress field, the Bajo Grande System (Panza, 1982, 1984) generating direct faulting combined with dextral movement, at a 110° azimuth, cutting and displacing the subvertical travertine bodies. These new fluid circulation channels end up lodging the quartz veins carrying silver and gold.